2012
DOI: 10.1002/nla.1827
|View full text |Cite
|
Sign up to set email alerts
|

Two‐grid methods for time‐harmonic Maxwell equations

Abstract: SUMMARYIn this paper, we develop several two‐grid methods for the Nédélec edge finite element approximation of the time‐harmonic Maxwell equations. We first present a two‐grid method that uses a coarse space to solve the original problem and then use a fine space to solve a corresponding symmetric positive definite problem. Then, we present two types of iterative two‐grid methods, one is to add the kernel of the curl‐operator in the fine space to a coarse mesh space to solve the original problem and the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The two-grid method was first introduced by Xu [44,45] and then applied to many problems, such as nonlinear elliptic equations [46], nonlinear parabolic equations [11,12], Navier-Stokes equations [23,29], eigenvalue problems [26,47,51] and also Maxwell equation [50]. It is worth noting that our two-grid method is different from the classical twogrid method for evolution problems [11,32,37].…”
Section: Introductionmentioning
confidence: 96%
“…The two-grid method was first introduced by Xu [44,45] and then applied to many problems, such as nonlinear elliptic equations [46], nonlinear parabolic equations [11,12], Navier-Stokes equations [23,29], eigenvalue problems [26,47,51] and also Maxwell equation [50]. It is worth noting that our two-grid method is different from the classical twogrid method for evolution problems [11,32,37].…”
Section: Introductionmentioning
confidence: 96%
“…Compared to the nonlinear Galerkin FE method, the two-grid method can save the CPU time and also get the almost the same errors and convergence rate to the one of nonlinear Galerkin FE method. In view of the advantages of two-grid method, the method has been developed by increasing researchers, the detailed contents can be found in Dawson and Wheeler [6], Chien and Jeng [9], Mu and Xu [8], Wu and Allen [13], Chen et al [10], Chen and Chen [12], Liu et al [14], Chen and Liu [15], Shi and Yang [7], Weng et al [16], Bajpai and Nataraj [18], Zhong et al [28], Liu et al [19], Liu et al [27], Yan et al [30] and some other references. Based on these discussions for two-grid method, ones can see that the time direction is approximated mainly by the second-order Crank-Nicolson (CN) scheme, the second-order two step backward difference (BD) method, and backward Euler (BE) method with first-order convergence rate.…”
Section: Introductionmentioning
confidence: 99%
“…The study [16] has shown that many of the standard Krylov-based techniques recommended for structural simulation or solid-state physics perform very poorly, or even fail, on the solution of generalized eigenproblems obtained by solving the curl-curl equation (1.1) with higher-order FEM. Slow convergence (or nonconvergence) and overall poor and inconsistent performance of the iterative solvers is one of the major problems, and makes the generalized eigenproblems arising in computational electromagnetics an open research problem that still presents fundamental challenges, even to very sophisticated numerical schemes [17,18]. Although a variety of Krylov methods can be used to compute small nonzero eigenvalues of generalized eigenvalue problems, many studies have shown that LOBPCG is one of the most effective at this task.…”
Section: Introductionmentioning
confidence: 99%